Organocatalytic Oxidative Dehydrogenation of Dihydroarenes by Dioxygen Using 2,3-Dichloro-5,6-dicyano-benzoquinone (DDQ) and NaNO2 - Hong Ma; Lipeng Zhou; Zhiqiang Sun; Jie Xu; Zhongtian Du; Hong Miao; Wei Zhang (Molecules, 2008)
The oxidative dehydrogenation of dihydroarenes catalyzed by 2,3-dichloro-5,6-dicyano-benzoquinone(DDQ) and NaNO2 with dioxygen is reported. The combination of DDQ and NaNO2 showed high efficiency and high selectivity, compared with other benzoquinones and anthraquinones, e.g., >99% conversion of 9,10-dihydroanthracene with 99% selectivity for anthracene can be obtained at 120 Ã‚Â°C under 1.3 MPa O2 for 8 h. Excellent results were achieved in the oxidative dehydrogenation of variety of dihydroarenes.